PENGEMBANGAN APLIKASI DELIVERY ORDER DI TAIWAN TEA HOUSE CSB MALL BERBASIS ANDROID - Yehuda bagaskara; Petrus Sokibi; Marsani Asfi (Universitas Catur Insan Cendekia (CIC) Cirebon, 2017)
Abstract Delivery order is an activity and provision of services where consumers order products supplied by producers and usually use a medium of communication by telephone or internet and the products ordered will be delivered to the consumers without consumers need to come and meet directly with the seller / producer. Android is a Linux-based operating system designed for touch screen mobile devices such as smart phones and tablet computers. Android was originally developed by Android, Inc., with financial support from Google, which then bought it in 2005. The operating system was released officially in 2007, in conjunction with the establishment of the Open Handset Alliance, a consortium of companies hardware, software, and telecommunications that promotes open standards mobile devices. The first Android phone went on sale in October 2008. Android-based delivery application order that currently used by Taiwan Tea House CSB Mall doesn’t have external database yet, which cost many problems. Development of this Android-based delivery order application at Taiwan Tea House CSB Mall that will be the end result of this essay is expected to solve those problems. Keywords : delivery order, Android, Linux, development, external database.